The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2023
DOI: 10.7717/peerj.15654
|View full text |Cite
|
Sign up to set email alerts
|

The prognostic significance of KLRB1 and its further association with immune cells in breast cancer

Abstract: Background Killer cell lectin-like receptor B1 (KLRB1) is an important member of the natural killer cell gene family. This study explored the potential value of KLRB1 as a breast cancer (BC) biomarker and its close association with the tumor immune microenvironment during the development of BC. Methods We examined the differential expression of KLRB1 in pan-cancer. Clinical and RNA-Seq data from BC samples were evaluated in The Cancer Genom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 51 publications
0
2
0
Order By: Relevance
“…KLRB1 is located on human chromosome 12 and encodes CD161 that is expressed on the surface of most NK cells and T lymphocytes ( 4 ). Studies have shown that inhibition of KLRB1 expression in breast invasive carcinoma is associated with impaired tumor immune function, leading to tumor progression and poor prognosis ( 28 , 29 ). Downregulation of KLRB1 expression is strongly associated with poor survival outcomes in EC and can influence tumor progression by affecting immune cell infiltration subpopulations in the TME ( 30 ).…”
Section: Discussionmentioning
confidence: 99%
“…KLRB1 is located on human chromosome 12 and encodes CD161 that is expressed on the surface of most NK cells and T lymphocytes ( 4 ). Studies have shown that inhibition of KLRB1 expression in breast invasive carcinoma is associated with impaired tumor immune function, leading to tumor progression and poor prognosis ( 28 , 29 ). Downregulation of KLRB1 expression is strongly associated with poor survival outcomes in EC and can influence tumor progression by affecting immune cell infiltration subpopulations in the TME ( 30 ).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, SPARC secreted by CAFs promotes tumor growth by inhibiting adhesion of triple-negative BC cells whilst stimulating invasion and metastasis [19]. Recently, KLRB1 has become an increasing focus in tumor research as it has been associated with tumor progression [11][12][13][14][15]20]. Xu and Huang et al found that KLRB1 is a tumor suppressor gene involved in the BC progression.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that KLRB1 gene inactivation enhances T-cell-mediated killing of glioma cells in vitro and the anti-tumor function of KLRB1 in vivo [ 13 ], whereas decreased KLRB1 expression has been associated with poor prognosis in BC patients [ 11 ]. Xu and Huang et al found that KLRB1 is in the down-regulation trend in BC and a negative correlation between overexpression of KLRB1 and poor prognosis (such as overall survival (OS) and recurrence free survival (RFS)) of BC patients through survival analysis [ 14 , 15 ]. However, not much is known about the relationship between KLRB1 expression and BC subtypes (such as the BRCA) progression.…”
Section: Introductionmentioning
confidence: 99%
“…[ 15 ] Currently, KLRB1 has shown potential biomarker value and immunomodulatory effects in breast cancer, esophageal squamous cell carcinoma, and glioma. [ 16 18 ] In addition, KLRB1 enhances the progression and evolution of gliomas through its unique effect on T-cell dysfunction. [ 18 ] However, the correlation between KLRB1 expression in TGCT and its biological function is unclear.…”
Section: Introductionmentioning
confidence: 99%